Bovine Platelet Proteins III. Some Properties of Platelet Fibrinogen - Solum, N. O; Łopaciuk, S (Thrombosis and Haemostasis, 1969)
1. Some properties of purified bovine platelet fibrinogen have been described and the data compared to those obtained by parallel analysis of purified bovine plasma fibrinogen.2. A close similarity was found between platelet and plasma fibrinogen as to sedimentation coefficients, electrophoretic mobilities in starch gel and polyacrylamide disc electrophoresis, light absorption spectra in the range 240 mμ to 330 mμ, ability to form immunoprecipitate with a rabbit antiserum against bovine plasma fibrinogen, total amino acid composition and in N-terminal amino acids.Differences between the fibrinogens were found as to intrinsic viscosity, carbohydrate content and behaviour upon clotting by thrombin. Intrinsic viscosity in 0.3 M NaCl at 25° was 0.48 dl/g for platelet fibrinogen as compared to 0.26 dl/g for plasma fibrinogen. The carbohydrate content of platelet fibrinogen was 0.56 ± 0.10% 1.56±0.10% and 1.37±0.09% for sialic acid (calculated as N-glycolyl neuraminic acid), hexose (galactose/mannose 1:2) and hexosamine (glucosamine), respectively. These values were 6, 54 and 26% higher than those found for plasma fibrinogen. The difference in clotting behaviour indicated a slower polymerization rate of the fibrin monomers formed from platelet fibrinogen than of those formed from plasma fibrinogen.